Studi Eksperimental Perpindahan Kalor dan Pengamatan Temperatur pada Mesin dan Radiator Kendaraan - Utomo Nugroho, Adrian; Nata Septiadi, Wayan; Astawa, Ketut (Teknik Desain Mekanika; Vol 10 No 2 (2021): April 2021 : Teknik Desain Mekanika, 2021)
Abstract Transportation is a vehicle for mankind to move something .All vehicles that use an engine as the main motor, there will always be an Internal Combustion proceses on the engine itself. Nowdays, most of the vehicle use a radiator in the purpose to release the engine heat. Every radiator will always using a fluid as the media to help the engine releasing the heat. This test is performed by dynamic and real conditions on the road with a motorcycle that comparing 3 fluids for the media. Fluids that are used for the test is: Radiator Coolant, Water (H2O), and Nanofluids (Al2O3-Air). The test result show that the heat exchange flow of Nanofluids (Al2O3-Air) has the best value if compared with Water (H2O) and Radiator Coolant. Keyword: Nanofluid, Radiator, Heat Exchange Flow, Alternate Working Fluid